Social brain networks: Resting-state and task-based connectivity in youth with and without epilepsy. (16th July 2021) - Morningstar, M.; French, R.C.; Mattson, W.I.; Englot, D.J.; Nelson, E.E.
Abstract: Individuals with epilepsy often experience social difficulties and deficits in social cognition. It remains unknown how disruptions to neural networks underlying such skills may contribute to this clinical phenotype. The current study compared the organization of relevant brain circuits—the "mentalizing network" and a salience-related network centered on the amygdala—in youth with and without epilepsy. Functional connectivity between the nodes of these networks was assessed, both at rest and during engagement in a social cognitive task (facial emotion recognition), using functional magnetic resonance imaging. There were no group differences in resting-state connectivity within either neural network. In contrast, youth with epilepsy showed comparatively lower connectivity between the left posterior superior temporal sulcus and the medial prefrontal cortex—but greater connectivity within the left temporal lobe—when viewing faces in the task. These findings suggest that the organization of a mentalizing network underpinning social cognition may be disrupted in youth with epilepsy, though differences in connectivity within this circuit may shift depending on task demands. Our results highlight the importance of considering functional task-based engagement of neural systems in characterizations of network dysfunction in epilepsy. Highlights: Connectivity in social brain networks differed in youth with and without epilepsy. Group differences in connectivity were noted during a social cognitive task. Youth with epilepsy had reduced prefrontal-temporal connectivity during the task. Groups differed in age-related changes in functional connectivity during the task.